Prophetic Leadership in Increasing the Quality of Education - Ach Qusairi; Abdullah Abdullah (Yayasan Avicenna, 2022)
The role of the leader is very important in the progress of an institution or agency. The leader is the driving force of all sources in an institution or agency, therefore the leader must have a good leadership capacity so that the goals of the institution or agency can be achieved. The focus of this research is how to implement prophetic leadership in improving the quality of education at MI Al-Husna Dawuhan Krejengan. The purpose of this study is to find out how the implementation of professional leadership in improving the quality of education at MI Al-Husna Dawuhan Krejengan. This research uses a qualitative approach method of case study type, which is located prophetically in MI Al-Husna Dawuhan Village, Krejengan District, Probolinggo Regency- East Java. The source of the data is the informant. Using primary and secondary data with data collection techniques through observation and interviews. The results of this study that the basis of the leadership of the Prophet applied by the head of the MI Al-Husna Dawuhan Krejengan madrasah is based on the mission of the Prophet Muhammad SAW, namely: the mission of humanization, the mission of liberation, the mission of plurality and tolerance, and moderation. The application of these 4 missions is carried out by applying the 4 qualities of the Prophet and Apostle, namely sidiq, amanah, tabligh and fathonah. the mission of liberation, the mission of plurality and tolerance, and moderation. The application of these 4 missions is carried out by applying the 4 qualities of the Prophet and Apostle, namely sidiq, amanah, tabligh and fathonah. the mission of liberation, the mission of plurality and tolerance, and moderation. The application of these 4 missions is carried out by applying the 4 qualities of the Prophet and Apostle, namely sidiq, amanah, tabligh and fathonah.